Gandhi; His Body and Politics - Yadav, Madan Ray (Nepal Journal of Multidisciplinary Research, 2023)
This article explores and analyses the charismatic leadership of M.K. Gandhi possessing the inspiring image in the Indian history. It concerns with the power of spirituality, knowledge of history and the self that gives people insights into life for the change and identification. Gandhi has been an icon who influences people to come up with dynamic-self. Being inspired by Leo Tolstoy and Buddha, Gandhi rightly understood the power of meditation, yoga, deep patience and incessant struggle that became the greatest weapon for him to uproot the tyrannical reign of the British from India. Based on Indic way; self, performance and rituals, the research explores and analyses the veiled fact of the sacrifices, passion and cognition of Gandhi, the body and its power. The performative body is acknowledged identical to the realized, knowledgeable and conscious body that helps people to understand the politics and the body of Gandhi that has been the synonymous of powerhouse and resourceful human power. Being vegetarian, truthful, sincere, obedient and revolutionary for the changes, Gandhi has been an inspiration and god man in India.